Penyelesaian Sengketa Tanah di Desa Bitahan Baru Kabupaten Tapin Melalui Mediasi oleh Kepala Desa - Yurizal Ath Thaariq; M. Febry Saputra (Jurnal Penegakan Hukum Indonesia, 2023)
From time to time, land disputes are an issue that often arises accompanied by community development, development, and the increasingly widespread access of various parties who make the authorized capital in the form of a piece of land for various purposes. Complaints about land issues are basically a phenomenon that questions a law related to land. The Village Head is obliged to resolve disputes that occur in the community. In this case, a land dispute is also a dispute that occurs in the community and therefore the Village Head has the right to be the mediator for the dispute. This research focuses on two formulations of the problem, namely how to implement land dispute resolution in Bitahan Baru Village by the Village Head and how the process of resolving land disputes in Bitahan Baru Village which aims to find out what method the Village Head provides as a mediator in dispute resolution problems and to provide legal certainty for the parties to the dispute to continue to carry out the win-win solution that has been given by the Village Head, especially in the Village.  New Bintahan Tapin County.It is a type of sociological juridical research using a qualitative approach, through library research and interviews then the data is analyzed using content analysis and the results of reports from this research are in the form of descriptive analytics. From this research, it was found that it is true that the obligation and authority in resolving disputes that occur in the community is the Village Head while still being guided by the applicable laws and regulations.